Upaya Meningkatkan Kecerdasan Naturalis Anak dengan Kegiatan Menanam Selada Menggunakan Media Tanam Hidroponik Melalui Manajemen PAUD Berkualitas Di TK Islam Terpadu Ibnul Mubarok Kota Palu - Carla Delvia Lembah; Nita Qonitiah Hifdziatul Fitri; Ricky Yoseptry; Siti Nur Janah; Dini Lidinillah (Jurnal Pendidikan dan Kewirausahaan)
Abstract: This study aims to improve children's naturalist intelligence in recognizing, maintaining and preserving the natural environment by implementing learning to plant lettuce at the Ibnu Mubarak Integrated Islamic Kindergarten on Veteran Street Taipalosi Alley, Tanamodindi, Mantikulore District, Palu Regency, Central Sulawesi using rokwel media. This study was motivated by the problem of children's low concern for the surrounding environment, the lack of land to foster children's interest in maintaining and preserving the surrounding environment so that children are less stimulated in developing their naturalist intelligence. This study uses a qualitative approach with the type of research design that will be used in this study is Classroom Action Research (CAR). Classroom Action Research (CAR) is a form of research conducted by teachers in their own classes. With the aim of improving and increasing expertise in the learning process, so that the learning process is more varied. This study uses qualitative research with the type of research being Classroom Action Research (CAR). This study was conducted through two cycles by following the stages of classroom action research procedures, namely: (1) planning, (2) implementation, (3) observation, (4) reflection. The data collection techniques used are observation and document study. The data analysis technique uses descriptive analysis. The subjects in this study were children in group B of TKIT Ibnul Mubarok Palu, totaling 11 children, consisting of 5 boys and 6 girls with an age range of 5-6 years. Based on the results of observations of teacher teaching activities in cycle I, the percentage value was 73.33% and increased in cycle II to 93.33%. The results of observations of children's learning activities in cycle I obtained a percentage value of 71.42% and increased in cycle II to 92.86%. In the results of children's learning in cycle I obtained a value of 72.73% and increased in cycle II to 90.91%. The conclusion of this study is that children's naturalist intelligence can be improved through planting activities with hydroponic planting media in group B of TKIT Ibnul Mubarok Palu.